A common origin for the fundamental plane of quiescent and star-forming galaxies in the EAGLE simulations. Issue 4 (12th November 2022) - de Graaff, Anna; Franx, Marijn; Bell, Eric F; Bezanson, Rachel; Schaller, Matthieu; Schaye, Joop; van der Wel, Arjen
ABSTRACT: We use the EAGLE cosmological simulations to perform a comprehensive and systematic analysis of the z = 0.1 fundamental plane (FP), the tight relation between galaxy size, mass, and velocity dispersion. We first measure the total mass and velocity dispersion (including both random and rotational motions) within the effective radius to show that simulated galaxies obey a total mass FP that is very close to the virial relation (10 per cent deviation), indicating that the effects of non-homology are weak. When we instead use the stellar mass, we find a strong deviation from the virial plane, which is driven by variations in the dark matter content. The dark matter fraction is a smooth function of the size and stellar mass, and thereby sets the coefficients of the stellar mass FP without substantially increasing the scatter. Hence, both star-forming and quiescent galaxies obey the same FP, with equally low scatter (0.02 dex). We employ simulations with a variable stellar initial mass function (IMF) to show that IMF variations have a modest additional effect on this FP. Moreover, when we use luminosity-weighted mock observations of the size and spatially integrated velocity dispersion, the inferred FP changes only slightly. However, the scatter increases significantly, due to the luminosity-weighting and line-of-sight projection of the velocity dispersions, and measurement uncertainties on the half-light radii. Importantly, we find significant differences between the simulated FP and observations, which likely reflects a systematic difference in the stellar mass distributions. Therefore, we suggest the stellar mass FP offers a simple test for cosmological simulations, requiring minimal post-processing of simulation data.